Inflation, Endogenous Market Segmentation and the Term Structure of Interest Rates - Casper De Vries; Xuedong Wang (Center for Economic Studies and ifo Institute (CESifo), 2015)
The term structure of interest rates does not adhere to the expectations hypothesis, possibly due to a risk premium. We consider the implications of a risk premium that arises from endogenous market segmentation driven by variable inflation rates. In the absence of autocorrelation in inflation, the risk premium is constant. If inflation is correlated, however, the risk premium becomes time varying and we can rationalize the failure of the expectations hypothesis. Indirect empirical tests of the model's implications are provided.
Keywords: E43; G12; 330; expectations hypothesis; term structure; time-varying risk premia; segmented markets; inflation